Diary of a wimpy kid Old school - Kinney, Jeff (Penguin Books Australia Melbourne, Vic., 2015)
Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive?